APPLICATIONS OF SOCIAL MEDIA TO LEARN SPEAKING: APPLICATIONS OF SOCIAL MEDIA TO LEARN SPEAKING - DEWI SRI KUNING (Universitas Muhammadiyah Kotabumi, 2020)
Abstract. Applications of Social Media to Learn Speaking. Social media is not a new things for the students right now. Many young generations that uses social media as the media to learn English, especially speaking. Generally, many applications in social media, as Youtube, Instagram, Facebook, Whatsapp, Telegram, Twitter, and so on that can be used by user to interact about all things in everywhere and everytime. Beside that, social media also has special applications to learn speaking, they are (1) Learn to Speak English with Busuu, (2)Hello English, (3) Learn English Daily, (4) Learn English Grammar Quickly, (5) English Listening and Speaking, (6) English Conversation Practice, (7) Memrise, (8) Duolingo, (9) ABA English, (10) Rosetta Stone, (11) Hello English Kids, (12) Voxy, (13) Basic English for Beginers, (14) Learn English. Speak English, and (15) Listen and Speak.